The role of work motivation in mediating the effect of perceived organizational culture on employee engagement - Fitria Khoirun Nisa'; Hardani Widhiastuti; Rusmalia Dewi (Proyeksi, 2026)
This study aims to analyze the effect of perceptions of organizational culture on employee engagement, with work motivation as an intervening variable, among employees of PT X. This study employs a quantitative approach using a saturated sampling technique, meaning that the entire population of 160 employees served as respondents. Data analysis was conducted using the Partial Least Squares-based Structural Equation Modeling (SEM-PLS) method. The results indicate that perceptions of organizational culture significantly influence employee engagement, with a coefficient value of 0.429 (T-statistic = 6.512; p-value = 0.000). Additionally, perceptions of organizational culture significantly influence work motivation with a coefficient of 0.494 (T-statistic = 9.344; p-value = 0.000). Work motivation was found to have a significant effect on employee engagement with a coefficient of 0.268 (T-statistic = 3.420; p-value = 0.000). The mediation test results indicate that work motivation significantly mediates the effect of organizational culture perception on employee engagement with a coefficient of 0.133 (T-statistic = 3.064; p-value = 0.001). The R-square value indicates that 53.1% of the variance in employee engagement is explained by the modelwhile 45.4% is explained by work motivation. Based on these results, it can be concluded that perceptions of organizational culture play a significant role in enhancing employee engagement, both directly and through work motivation as a mediator.